In vitro Salt Tolerance of Safflower (Carthamus tinctorius L.) Genotypes using Different Explants - Hamedi, Mahdi; Golkar, Pooran; Arzani, Ahmad (Plant Tissue Culture and Biotechnology, 2016)
To evaluate the response of different genotypes of safflower (Carthamus tinctorius L.) to in vitro salt stress was conducted. Callus derived from leaflet, pedicel, hypocotyls, and adaxial and abaxial surfaces of the leaf were subjected to in vitro salt stress at 0, 100 and 200 mM of NaCl. The relative growth rate (RGR), callus growth rate (CGR), relative water content (RWC), tolerance index (TOL) and necrosis percentage were assessed. Results of analysis of variance indicated significant effects of salt stress, significant differences among genotypes for all traits and significant genotype × salt stress interaction for CGR, RWC and necrosis traits. The application of NaCl decreased RGR, CGR, RWC and TOL, significantly, while a significant increase observed across all the tested explants and genotypes for necrosis percentage data. An Iranian safflower genotype (K21) superior for RGR, RWC and TOL was the most salt tolerant genotype at the cellular level. Plant Tissue Cult. & Biotech. 26(2): 231-242, 2016 (December)